A Student-Focused Study: Strategy of Text Summary Writing and Assessment Rubric - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2016)
writing helps students to determine the main idea, make generalizations, eliminate trivial details, restate the ideas entirely and enables students to remember any information. In the present study, a mixed method is used. In the scope of the research, a strategy of text summary writing is developed. In order to develop text summary writing strategy, four-weeks implementation is applied to 43 students studying at the university 3rd grade by the researchers. The strategy developed in these implementations have been updated in the education period with students' feedback and finalized with student-focused changes. At the end of the study, it is stated that the students who have taken text summary writing strategy education, able to summarize without taking direct quotations from the main text, use less time while writing the summary, write shorter summaries and nearly all of the students agreed that summary writing education is useful. It is concluded that conducting a systematic and planned text summary writing education helps students to improve written expression skill.
Keywords: Text summary; Summary writing skill; Text summary assessment; Rubric; LEARNING-ACTIVITY